2022
DOI: 10.3389/fpsyt.2022.773100
|View full text |Cite
|
Sign up to set email alerts
|

The Psychological Challenges of Emergency Medical Service Providers During Disasters: A Mini-Review February 2022

Abstract: The provision of emergency medical services (EMS) is an inherently stressful job. Depression, anxiety, and posttraumatic stress disorder (PTSD) are common psychological challenges affecting EMS providers. As disasters increase worldwide, the need for EMS also increases, as they are an essential part of any disaster management system. Studies have shown that EMS providers experience psychological challenges due to disaster response without receiving the needed psychological support. There is a scarcity of resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…According to the literature, PTSD can result in other mental disorders, including substance abuse, and anxiety disorders [ 15 ], interfere with the daily life performance, compromise a person's health performance, and finally, increase the risk of mental health disorders and physical diseases [ 16 ]. Therefore, the psychological consequences of disaster response can advance towards chronic mental illnesses, and as a result, negatively influence one's job performance [ 17 ]. Several studies have investigated the rate of post-traumatic stress disorders in a group of health care professionals involved in the earthquake response engaged in earthquake response [ 10 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature, PTSD can result in other mental disorders, including substance abuse, and anxiety disorders [ 15 ], interfere with the daily life performance, compromise a person's health performance, and finally, increase the risk of mental health disorders and physical diseases [ 16 ]. Therefore, the psychological consequences of disaster response can advance towards chronic mental illnesses, and as a result, negatively influence one's job performance [ 17 ]. Several studies have investigated the rate of post-traumatic stress disorders in a group of health care professionals involved in the earthquake response engaged in earthquake response [ 10 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that EMS providers experienced many challenges during pandemic as frontline workers. However, there is still a scarcity of research focusing on EMS providers psychological challenges during COVID-19 in many parts of the world [ 51 ]. Our study showed prevalence of psychosocial stress and health risk in EMS professionals working around the clock in EMS agencies before and during pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed prevalence of psychosocial stress and health risk in EMS professionals working around the clock in EMS agencies before and during pandemic. More research may be conducted on EMS personnel mental health perspectives and needs before and during pandemic [ 51 ]. This type of research will help prepare the EMS work force for any future pandemic based on the lessons learned.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, EMS plays a substantial role in disaster management activities and is considered an essential part of any disaster management system. 11 Human-made and natural disaster numbers have been increasing during the last decade. 12 In times of disaster, the use of EMS services was significantly greater than in normal times.…”
Section: Introductionmentioning
confidence: 99%